2004
DOI: 10.1097/01.rct.0000131583.52386.cf
|View full text |Cite
|
Sign up to set email alerts
|

Bronchobiliary Fistula After Liver Transplantation

Abstract: This report describes the imaging findings of the first reported case of a bronchobiliary fistula that developed as a complication of liver transplantation. The diagnosis was confirmed by the aspiration of bile from the bronchus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…She developed biliary stricture and right subphrenic bile collection leading to BBF, for which she underwent percutaneous transhepatic biliary drainage (PTBD) [ 4 ]. A similar case was reported by Yeatman et al [ 5 ]. The likely mechanism of the development of BBF in a post-LT setting is hypothesized to be because of the biliary stricture and bile leak in the subphrenic space, where bile acts as a tissue-corrosive agent, leading to the erosion of the diaphragm and subsequent communication with the right-hand bronchial tract.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…She developed biliary stricture and right subphrenic bile collection leading to BBF, for which she underwent percutaneous transhepatic biliary drainage (PTBD) [ 4 ]. A similar case was reported by Yeatman et al [ 5 ]. The likely mechanism of the development of BBF in a post-LT setting is hypothesized to be because of the biliary stricture and bile leak in the subphrenic space, where bile acts as a tissue-corrosive agent, leading to the erosion of the diaphragm and subsequent communication with the right-hand bronchial tract.…”
Section: Discussionsupporting
confidence: 86%
“…In 1850 Peacock et al [ 1 ] reported the first BBF case in a young woman with a ruptured hydatid cyst. Both the acquired and the congenital varieties of BBF are very rare complications in children [ 2 - 5 ]. Acquired BBF usually occurs as a complication of a rupture of a hydatid cyst or subphrenic abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a rare complication that may appear in the natural history of liver hydatid disease or after its surgical treatment [1, 2], trauma [3], congenital malformation [46], tumor [7], surgery [810], biliary lithiasis [11], hepatic abscess [12], liver transplantation [13], or even radiofrequency treatment [14, 15]. …”
Section: Introductionmentioning
confidence: 99%